Research-Based Strength-Based Teaching and Support Strategies for Twice-Exceptional High School Students with Autism Spectrum Disorder - Sally M. Reis; Sara J. Renzulli (Behavioral Sciences)
In the last five years, several scholars have collaborated in an integrated research program focused on students identified with both academic talents and autism spectrum disorder (2eASD) with support from a Javits Gifted and Talented Students Education grant. Several different empirical studies were initiated and completed during this period, investigating the ways in which some of these twice-exceptional students have been able to be successful in secondary school and highly competitive colleges. In this article, we summarize findings from several of these studies, synthesizing implications and recommendations with a goal of offering research-based practices, especially related to healthy social and emotional development and strong academic achievement in students identified as 2eASD.